Neo Synergy Training Centre (NSTC) Online Registration System - Mohd Taher, Nurul Uyun (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Motivation is one of the strong factors that lead to one’s success. Motivation allows people to achieve more than they expect and it sometimes costs thousands for the company to provide motivational courses to the public. Therefore, Neo Synergy Training Centre or known as NSTC has comes about. With the aims of providing motivational courses, consultation, training, seminar and talks, Neo Synergy Training Centre is utilising the fast growing technology which is website. However, the process of applying for new membership as a medium to become facilitators is still using the manual form and causes some inefficient task to the admin, costing time and money. Besides, the payment and collection of annual fees also often overdue. In order to overcome these problems, this is where Neo Synergy Training Centre Online Application System is developed. With the system, the process of managing the application of new members could be enhance in more efficient ways. Thus, save time and money. In this report, we could see the details on the development of this project.